Exploring The Impacts of Mobile Phone Addiction on Physical Activities Short Sports Video: A Multi-Method Systematic Review - Bai Kuotian; Syed Kamaruzaman Syed Ali, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2025)
In today’s hyperconnected world, understanding how mobile phone usage shapes student well-being has become increasingly important. As mobile phones become deeply embedded in students' lives, their impact on health, behaviour, and social interactions demands critical academic attention. This study investigates the relationships between mobile phone addiction, physical activity, interpersonal relationships, and short sports video consumption among Chinese college students. A systematic review, conducted in accordance with Preferred Reporting Items of Systematic Reviews and Meta-Analyses (PRISMA) guidelines, involved comprehensive searches across PubMed, Web of Science, and Scopus to synthesize both quantitative and qualitative findings; where applicable, a meta-analysis was conducted to statistically integrate the quantitative results. Study determined perceived benefits of mobile phone use, negative consequences of addiction, barriers to physical activity, impact on interpersonal relationships, and the role of short sports videos. While mobile phones can enhance academic performance and connectivity, excessive use is correlated with academic decline, poor sleep, physical health issues, and disrupted daily functioning. Addiction also limits physical activity and reduces the quality of interpersonal relationships, resulting in superficial connections and increased social isolation. Notably, the study identifies a dual role of short sports videos as a motivator for physical activity and a contributor to digital dependency an underexplored dimension in the existing literature. Thus, study recommend promotion of digital wellness programs, encouraging self-regulation, enhancing digital literacy, and integrating guided physical activity via mobile platforms to foster healthier digital habits and support student well-being.